IoT 기술을 활용한 에너지 절약형 전등점멸 초인종 설계 - 유호균(Ho-Gyun You); 김예은(Ye-Eun Kim); 김희정(Hee-Jeong Kim); 장우희(Woo-Hee Jang); 국중진(Joongjin Kook); 이광재(Kwangjae Lee) (전기학회 논문지 P권, 67(2), 2018)
This paper is a system that visually informs the hearing impaired to visit other people by blinking the light of a room using the IoT(Internet of Things) technology. The system combines the power of home-use lights with low-power IoT devices to provide visual notifications. Using a current sensor, this system can track user location and then turns on and off the light in that room only to save energy. The proposed idea can create a society that is equal to everyone and can live more conveniently.